Conceptualising an integrated framework for social responsibility of Islamic finance within a three-sector economic model - Barom, Mohd Nizam (2019)
The conception of Islamic economics is strongly underpinned by normative foundations with the aim of realising socio-economic justice and the betterment of the human well-being. The emergence of Islamic banking and finance was then touted to be the operational aspect of Islamic economics to achieve this novel aspirations. Nevertheless, there was a contentious debate on the responsibility of Islamic financial institutions (IFIs) to bear this social role. Many industry players argued that IFIs are entities within the commercial sector of the economy, and therefore should not be burdened by these social roles. Instead,the public sector should be the most appropriate institution to address the issues along with the non-profit sector, highlighting a clear demarcation and dichotomy between these three available sectors in the economy, i.e. public sector, commercial sector and voluntary or ‘third’ sector. Despite current debates which signify an increasing acceptance of IFIs on their expected role of social responsibilities, there is still an absence of a general framework to be used as a foundation for the interaction between these three sectors. Hence, this research sets out to conceptualise an integrated framework for social responsibility of Islamic finance within a three-sector economic model consistent with the cooperative spirit and collective responsibility imbued in the ethical ideals of Islamic economics. In addition to the literature in Islamic economics and finance, this research also benefits from the literature of voluntary sector and uses an integrated three-sector economic framework to provide a conceptual framework of potential interaction between the commercial sector, particularly in the context of the Islamic banking and finance industry with the public and voluntary sector in the economy in a cooperative and harmonious spirit. This integrated framework is expected to create a conducive set-up to facilitate stronger social responsibility commitment among the Islamic finance industry as a constituent of the commercial sector along other sectors in the economy to cooperatively contribute to the betterment of human well-being and socio-economic justice in a more effective and systematic manner.